Problems of Long Survival Following Surgery in Patients with NonBNonC-HCC: Comparison with HBV and HCV Related-HCC - Hiwatashi, Kiyokazu (Ivyspring International Publisher, 2015)
Background: The number of patients with hepatocellular carcinoma (HCC) in the absence of both hepatitis B virus surface antigen (HBsAg) and hepatitis C virus antibody (HCVAb) (NBNC-HCC) has been rapidly increasing in Japan. The objective of this study was to compare the clinical and pathological characteristics between patients with the NBNC-HCC, those with HBsAg positive HCC (B-related HCC) and HCVAb positive HCC (C-related HCC). A better understanding will facilitate the development of postoperative strategies to better manage patients with NBNC-HCC.